2021
DOI: 10.21608/jabps.2021.74208.1128
|View full text |Cite
|
Sign up to set email alerts
|

A review on the chemical and biological properties of the Amaryllidaceae alkaloid, narciprimine (1968-2020)

Abstract: Amaryllidaceae occupies a prominent position among the most important alkaloid-rich plant families in the globe. Plants of this family show an exceptional ability to produce a myriad of structurally diverse alkaloids with noteworthy pharmacological and therapeutic potential. Of these alkaloids, narciprimine is a rare weakly basic phenanthridone alkaloid that was identified from some species belonging to the genera Cyrtanthus, Galanthus, Lycoris, Narcissus, and Zephyranthes. This alkaloid has attracted a lot of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Chemotaxonomic Significance of the Isolated Phytocompounds. Extensive literature review pertaining to the characterized metabolites 1−16 indicated that only lycorine (1) was previously isolated from H. vittatum bulbs, 6,26 whereas the phenanthridone derivative, narciprimine (15), which was described from a range of Amaryllidaceae plants, e.g., Cyrtanthus, Galanthus, Lycoris, Narcissus, and Zephyranthes species, 12 is first obtained herein from plants of the genus Hippeastrum. Likewise, among different members of the Amaryllidaceae, 3′-methyl isoliquiritigenin (2) was only reported from Crinum augustum Rox.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemotaxonomic Significance of the Isolated Phytocompounds. Extensive literature review pertaining to the characterized metabolites 1−16 indicated that only lycorine (1) was previously isolated from H. vittatum bulbs, 6,26 whereas the phenanthridone derivative, narciprimine (15), which was described from a range of Amaryllidaceae plants, e.g., Cyrtanthus, Galanthus, Lycoris, Narcissus, and Zephyranthes species, 12 is first obtained herein from plants of the genus Hippeastrum. Likewise, among different members of the Amaryllidaceae, 3′-methyl isoliquiritigenin (2) was only reported from Crinum augustum Rox.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the overview of phytochemical data on H. vittatum has revealed its ability to accumulate a variety of chemical metabolites, of which alkaloids represent the major class identified so far, e.g., belladine-, crinine-, galanthamine-, haemanthamine-, homolycorine-, lycorine-, narciclasine-, and tazettine-types, whereas the nonalkaloidal principles produced by this valued species have remarkably received much lesser attention. Therefore, as part of our research interest in different plants belonging to the family Amaryllidaceae, ,− this work investigates the nonalkaloidal metabolites, the phenolic and flavonoidal contents, and the antioxidant potential of H. vittatum bulbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation